2020
DOI: 10.1089/mdr.2020.0146
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant CTX-M and CMY-2 Producing Escherichia coli Isolated from Healthy Household Dogs from the Great Metropolitan Area, Costa Rica

Abstract: Objective: This study aimed to determine the prevalence of fecal carriage of antibiotic-resistant Escherichia coli of healthy household dogs with an emphasis on extended-spectrum b-lactamases (ESBL), AmpC-type blactamases and resistance to quinolones. Materials and Methods: Rectal swabs were collected from 74 dogs without any clinical evidence of gastrointestinal disease. Samples were cultured on MacConkey agar plates and MacConkey supplemented with 2 mg/mL cefotaxime or 5 mg/mL ciprofloxacin. Isolates were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…CMY-2 is the most common type of plasmid AmpC β-lactamase found in Enterobacteriaceae throughout the world, in isolates from human and animal origin. In this study, it was identified in eight isolates, which is in concordance with most research studies performed in the various countries, including Portugal [ 2 , 8 , 27 , 45 , 61 , 87 , 88 , 89 ].…”
Section: Discussionsupporting
confidence: 89%
“…CMY-2 is the most common type of plasmid AmpC β-lactamase found in Enterobacteriaceae throughout the world, in isolates from human and animal origin. In this study, it was identified in eight isolates, which is in concordance with most research studies performed in the various countries, including Portugal [ 2 , 8 , 27 , 45 , 61 , 87 , 88 , 89 ].…”
Section: Discussionsupporting
confidence: 89%
“…Whole-genome sequencing studies also show that some STs, and closely related strains within these STs, are carried by both dogs and humans [16, 21–23]. Carriage of genes encoding resistance to clinically important antibiotics is also reported [24–26].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study revealed high levels of antimicrobial susceptibility for E. coli isolated from fecal samples of Baird’s tapirs ( Tapirus bairdii ) from Costa Rica, which results contrast from the ones of this study (59.0% of meropenem-resistant E. coli isolates) ( Rojas-Jiménez et al, 2019 ). Also, in a study performed on house-hold dogs, no isolates revealed a resistance phenotype against carbapenems ( Rodríguez-González et al, 2020 ). On the other hand, high levels of resistance towards this antimicrobial class were previously detected in clinical isolates of Pseudomonas aeruginosa (63.1%) from some of the main hospitals in San Jose ( Toval et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise concern due to the medical importance of these antimicrobials (carbapenems (meropenem), fluoroquinolones (enrofloxacin), and third-generation cephalosporins (ceftazidime)) for both human and veterinary medicine, including wildlife ( Vittecoq et al, 2016 ; McEwen & Collignon, 2018 ; Baros Jorquera et al, 2021 ). Resistance to cephalosporins, including ceftazidime was recently detected in E. coli isolates in healthy household dogs from Costa Rica ( Rodríguez-González et al, 2020 ). Previous research also revealed high levels of AMR towards first generation cephalosporins and enrofloxacin in clinical samples of food-producing animals in Costa Rica ( Mayorga et al, 2015 ; Andino-Molina et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%